Digital Car Showroom Business Strategy in the Automotive Industry: Its Impact on Consumer Behavior in PT. Carro Indonesia - Muhammad Fahmi Fahrurrodzi; Raden Aswin Rahadi (Publikasi Indonesia, 2024)
This study aims to identify consumer behavior towards the development of business models carried out by showrooms and dealers, especially Carro Indonesia which is based on digital startups, and create a strategic position to gain a competitive advantage in the car buying and selling industry. To analyze the environmental factors of this business externally using PESTEL and Porter's 5 strengths, then internal analysis through VRIO and SWOT. This research method uses qualitative and quantitative methods, with data collection conducted online and offline, using in-depth interviews and questionnaires. Data analysis was conducted using content analysis and Analytical Hierarchy (AHP) survey process. As for determining critical adoption factors for consumer behavior in buying a car by doing 4 criteria and 15 sub-criteria. AHP is a methodical framework that establishes a hierarchical structure with interdependent layers, analyzes the weights of various aspects, and evaluates potential actions with regard to existing structures. AHP has been used to prevent contradictory situations in research. As a result, interview data must be presented in quantitative form, i.e. how AHP ensures consistency of its findings because statements in qualitative interviews can be weighted. Then from the results of this study, each stakeholder can use this research as a basis for decision making to determine the company's steps to increase the level of adoption of services that are used as company products that are in accordance with the car buying and selling market.